Determination of pre-service science teachers’ attitudes towards reading science texts - Şendil Can; Gülperi Öztürk (International Journal of Evaluation and Research in Education (IJERE), 2019)
The purpose of the current study is to determine the effects of the variables such as gender, grade level, grade point average and book reading frequency on pre-service science teachers’ attitudes towards science texts. The sampling of the current study is comprised of 103 pre-service science teachers enrolled at the Education Faculty of Muğla Sıtkı Koçman University in the spring term of 2017-2018 academic year. In the current study, in order to determine the pre-service teachers’ attitudes towards reading science texts, “The Scale of Attitudes towards Reading Science Texts” was used. The effects of gender and grade level on the pre-service science teachers’ attitudes towards reading science texts were analyzed with independent samples t-test and the effects of academic achievement and book reading frequency were analyzed with one-way variance analysis (ANOVA). As a result of the study, it was concluded that the gender and grade level variables have significant effects on the pre-service teachers’ attitudes towards reading science texts in the sub-dimensions of making use of science texts when possible, denial and contribution of reading science texts to learning and skills and that the general grade point average and book reading frequency have significant effects on the pre-service teachers’ attitudes towards reading science texts in the sub-dimension of making use of science texts when possible.